PHOTODYNAMIC THERAPY OF MACULAR DEGENERATION - Davorin Sevšek (Zdravniški Vestnik, 2004)
Background. University Eye Clinic in Ljubljana began to perform a photodynamic therapy (PDT) in July 2002. Up to September 2003 there were 51 PDT interventions on 36 eyes. Almost half of the eyes had one or more reinterventions. PDT was used on 29 eyes with age related macular degeneration (AMD). Just before the treatment all of them had visual acuity (VA) 6/60 or better and there were predominantly classical or classical choroidal neovascular (CNV) membranes. Most VA did not changed significantly in follow-up visits but diameter of CNV membranes was obviously reduced. In macular degeneration due to pathologic myopia (MMD), photodynamic therapy was performed on 7 eyes with mainly occult CNV and VA was 12/60 or better. VA was mostly better in follow-up visits than before treatment with PDT. Conclusions. There were no serious complications during and after PDT interventions. Two patients had back pain during the infusion of Verteporfin but there was no need to stop the intervention.